Uma Proposta de Autoavaliação e Avaliação por Pares em Modelagem na Educação Matemática - Pacheco, Sibeli Mallmann (2020)
Discussions about evaluation in Mathematics Education have been increasingly recurrent, and permeate numerous approaches or ways of teaching and learning mathematics, such as Mathematical Modelling. However, there is still little research that shed light on ways of evaluating students in Mathematical Modelling tasks, which makes it imperative to develop investigations supported by the view of teachers familiar with the subject. In view of this gap in the area and the particular interest in understanding evaluation within the scope of Modelling, a synthesis of what is sought through the research question has been reached: What is shown by a proposal for Self-Assessment and Peer Review - PSA - for teachers familiar with Mathematical Modelling? Guided by this question, we assumed qualitative research from a phenomenological perspective, listening to teachers familiar with Modelling, and interpreting the meaning of what was shown, when using an evaluation proposal (form) based on the principles of Self-Assessment and Peer Review - PSA . To this end, we will consider forms produced for the research based on the testimonies of teachers about their experience with this proposal - with their feedback with opinions, suggestions and audio recordings, as a way to help understand what is revealed from the PSA evaluation method in Mathematical Modelling, according to the perspective of these subjects. We proceed according to the phenomenological perspective, highlighting units of meaning and seeking convergence of the senses among them, using the qualitative analysis software, Atlas.ti, as a facilitator of the analysis. The research culminated in two open categories: 1) An Evaluation Conception and 2) Proposal as a Procedure and an Evaluation Instrument. The interpretations of the open categories showed the potential of the proposal, since it is in line with what is conceived and developed in Modelling. They also clarify fragile aspects regarding personal and student actions, in the task management and the ethical issues arising from the assessment change.